Neural correlates of speech processing in prelingually deafened children and adolescents with cochlear implants. - Magdalene Ortmann (Public Library of Science (PLoS), 2013)
Prelingually deafened children with cochlear implants stand a good chance of developing satisfactory speech performance. Nevertheless, their eventual language performance is highly variable and not fully explainable by the duration of deafness and hearing experience. In this study, two groups of cochlear implant users (CI groups) with very good basic hearing abilities but non-overlapping speech performance (very good or very bad speech performance) were matched according to hearing age and age at implantation. We assessed whether these CI groups differed with regard to their phoneme discrimination ability and auditory sensory memory capacity, as suggested by earlier studies. These functions were measured behaviorally and with the Mismatch Negativity (MMN). Phoneme discrimination ability was comparable in the CI group of good performers and matched healthy controls, which were both better than the bad performers. Source analyses revealed larger MMN activity (155-225 ms) in good than in bad performers, which was generated in the frontal cortex and positively correlated with measures of working memory. For the bad performers, this was followed by an increased activation of left temporal regions from 225 to 250 ms with a focus on the auditory cortex. These results indicate that the two CI groups developed different auditory speech processing strategies and stress the role of phonological functions of auditory sensory memory and the prefrontal cortex in positively developing speech perception and production.